1998
DOI: 10.1021/bi980356b
|View full text |Cite
|
Sign up to set email alerts
|

Folding Kinetics of a Fluorescent Variant of Monomeric λ Repressor

Abstract: A tryptophan-containing variant of monomeric lambda repressor has been made, and its folding kinetics were analyzed at 20 degreesC using fluorescence stopped-flow and dynamic NMR. Equilibrium denaturation curves obtained by circular dichroism, fluorescence, and NMR are superimposable. Stopped-flow analysis indicates that in the absence of denaturants the folding reaction is complete within the dead-time of the experiment. Within higher denaturant conditions, where the folding rate is slower, NMR and stopped-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…A fast-folding mutant, hereafter abbreviated as '' Q33Y ,'' is studied here. The mutations are Glu-33 3 Tyr, Tyr-22 3 Trp (to allow fluorescence detection), Gly-46 3 Ala, and Gly-48 3 Ala (10,(17)(18)(19). The protein was expressed and purified as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…A fast-folding mutant, hereafter abbreviated as '' Q33Y ,'' is studied here. The mutations are Glu-33 3 Tyr, Tyr-22 3 Trp (to allow fluorescence detection), Gly-46 3 Ala, and Gly-48 3 Ala (10,(17)(18)(19). The protein was expressed and purified as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…T he nature of the energy landscape when folding occurs on the microsecond timescale continues to be investigated using both experimental and computational approaches. The 80-residue subdomain of the λ-repressor transcription factor, λ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), is an appealing system as it contains five α-helices arranged in a nonsymmetric pattern, folds in microseconds, and is nearly a downhill folder (12), a condition where a continuous series of folding events may be characterized. These characteristics along with a folding time that nears the upper limit for current all-atom simulations (13)(14)(15)(16)(17)(18)(19) make this protein appropriate for detailed comparisons between experiment and simulations.…”
mentioning
confidence: 99%
“…Oas and coworkers found that the wild type and a fasterfolding mutant with two helix-promoting substitutions (λ AA with G46A/G48A, Fig. S1A) fold cooperatively (1)(2)(3)(4). The transition state ensemble (TSE) characterized using ϕ analysis minimally contains α1 and α4 (3).…”
mentioning
confidence: 99%
“…We chose λ*YA, the Y22W/Q33Y/G46,48A mutant of λ-repressor fragment 6-85, as our model protein (11,12). Tryptophan W22 provides a fluorescent probe (11).…”
mentioning
confidence: 99%
“…We chose λ*YA, the Y22W/Q33Y/G46,48A mutant of λ-repressor fragment 6-85, as our model protein (11,12). Tryptophan W22 provides a fluorescent probe (11). Based on the crystal structure, tyrosine Y33 enhances the fluorescence lifetime difference between folded and unfolded states by contact quenching W22 when the protein is folded (13).…”
mentioning
confidence: 99%